2020
DOI: 10.1007/s10270-020-00811-8
|View full text |Cite
|
Sign up to set email alerts
|

Exploring how users engage with hybrid process artifacts based on declarative process models: a behavioral analysis based on eye-tracking and think-aloud

Abstract: Process design artifacts have been increasingly used to guide the modeling of business processes. To support users in designing and understanding process models, different process artifacts have been combined in several ways leading to the emergence of the so-called "hybrid process artifacts". While many hybrid artifacts have been proposed in the literature, little is known about how they can actually support users in practice. Objective: To address this gap, this work investigates the way users engage with hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 60 publications
(108 reference statements)
0
1
0
Order By: Relevance
“…This approach provided more profound insights into participant behavior and their challenges during task performance. For example, it was shown that DCR Graphs (declarative process models based on directed graphs) helped users gain an overview of the business process [18]. In other fields, such as usability, the think-aloud method is widely used due to its benefits in revealing cognitive processes [19,20].…”
Section: Related Workmentioning
confidence: 99%
“…This approach provided more profound insights into participant behavior and their challenges during task performance. For example, it was shown that DCR Graphs (declarative process models based on directed graphs) helped users gain an overview of the business process [18]. In other fields, such as usability, the think-aloud method is widely used due to its benefits in revealing cognitive processes [19,20].…”
Section: Related Workmentioning
confidence: 99%
“…overview in [14]). This research delves into various aspects associated with the representation of process models and process data (e.g., [2,3,4,7,15,17,33]), users' background and expertise (e.g., [29,35]), the tasks in which the models are used (e.g., [38,27]) and the tools supporting these tasks (e.g., [37,1,26]). Many of these aspects have been shown to have a significant impact on the comprehension of process models [14].…”
Section: Related Workmentioning
confidence: 99%